IoT-Based Smart Home Switch System Using the ESP32 Microcontroller - Lawrence, Scovien Olle; Muhammad Soomro, Dur (Evolution in Electrical and Electronic Engineering, 2022)
Nowadays, people tended to forget to turn off their appliances, particularly those that used a lot of electricity at home, resulting in a significant increase in their monthly electricity bill. Some people could not walk to turn on and off the appliances because of their health conditions, which forces them to either leave the appliances on or ask others to assist, and they were not always by their side when they needed it most. In this current period of technological advancement, most people were addicted to automatic devices, believing that these could simplify their daily life, particularly at work. This project was accomplished through the internet of things (IoT), which provides consumers with a higher level of living comfort. A smart home switch system based on IoT using an ESP32 microcontroller was developed in this project to make people’s lives easier, particularly for those who were disabled. Even if they were away from home, they could save time by turning on and off electrical appliances and assisting people who were in need to complete their daily tasks more conveniently. The switches for this smart technology were operated by an online server accessible via a mobile device or a personal computer. The Blynk Application and an ESP32 microcontroller controlled lights and other electrical appliances. Users could control the appliance manually or online, depending on the user preference, and it provided updates to the Blynk controlled panel regarding their state.